Determinants of the use of technical assistance by Brazilian family famers in 2014 - Rocha Junior, Adauto Brasilino; de Freitas, Jacy Alves; Cassuce, Francisco Carlos da Cunha; Costa, Silvia Maria Almeida Lima [UNESP] (FapUNIFESP (SciELO), 2019)
This paper analyzes the determinants of the use of technical assistance by Brazilian family farmers in 2014. Using data from the National Survey by Household Samples (PNAD) of 2014, a qualitative probit regression model was estimated, allowing the identification of the magnitude and significance of the effect of each explanatory variable on the probability of using technical assistance in the last agricultural work developed in the enterprise. The results show that the socioeconomic profile, the productive characteristics and the location of the family farmer affect significantly the probability of using technical assistance. It was observed that the fact that an individual with non-white skin, who has as main marketing channel direct sale to the consumer, be transferee or present unspecified condition in relation to the land, has advanced age or low education or income per capita has a statistically significant effect of reducing the probability of using technical assistance. On the other hand, the fact that the individual has as a main marketing channel the sale to companies or cooperatives, has temporary employees or he/she is located in the south region increases this probability. It is concluded, finally, that in-depth studies to better understand these effects can provide support for the improvement of technical assistance actions.
Análise dos determinantes da utilização de assistência técnica por agricultores familiares do Brasil em 2014
Keywords: Ater; Family farming; Technical assistance; Technical capacitation